2007
DOI: 10.1093/annonc/mdm056
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pain in patients with cancer: a systematic review of the past 40 years

Abstract: Background: Despite the abundant literature on this topic, accurate prevalence estimates of pain in cancer patients are not available. We investigated the prevalence of pain in cancer patients according to the different disease stages and types of cancer.Patients and methods: A systematic review of the literature was conducted. An instrument especially designed for judging prevalence studies on their methodological quality was used. Methodologically acceptable articles were used in the meta-analyses.Results: F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
889
4
42

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,636 publications
(959 citation statements)
references
References 170 publications
24
889
4
42
Order By: Relevance
“…9,11,[13][14][15] In this study, the main complaint in the emergency room was pain, similar to that reported in a 2007 systematic review. 16 However, even with the recommendation of the World Health Organization (WHO) 17 and the Brazilian MH, 7 as well as a high probability of success in pain control, this symptom is still neglected worldwide. 18 Knowledge and skills development for adequate pain management should be a priority for health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,[13][14][15] In this study, the main complaint in the emergency room was pain, similar to that reported in a 2007 systematic review. 16 However, even with the recommendation of the World Health Organization (WHO) 17 and the Brazilian MH, 7 as well as a high probability of success in pain control, this symptom is still neglected worldwide. 18 Knowledge and skills development for adequate pain management should be a priority for health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…39 The seemingly lower pain severity in our study compared with that of other studies was noteworthy. 3 Possible reasons for this include Asians' reluctance to report pain because of cultural influences, 34,[40][41][42][43] possible selection bias from attrition, and unique practice characteristics of pain management and palliative care referral in Korea. 18 The current study had limitations.…”
Section: Original Articlementioning
confidence: 99%
“…1 Pain is reported by 60% to 70% of patients with advanced cancer 2,3 and increases as patients approach death. 4 Fortunately, in the vast majority of cases, adequate pain control can be achieved by using the World Health Organization guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Pain is common among persons with advanced cancer, [5][6][7] with studies finding that 75%-90% of those with advanced cancer report severe pain throughout their illness. 8,9 In CRC, mechanisms of pain include tumor infiltration of nerves, bowel obstruction, treatment-induced neuropathy, and hepatic capsular distention, among others.…”
Section: Introductionmentioning
confidence: 99%